Managing an aging workforce: what is the value of human resource management practices for different age groups of workers? - Pinto, A.; Ramos, S.; Nunes, S.M.M.D. (TÉKHNE - Review of Applied Management Studies, 2014)
Demographic aging trends will have consequences concerning the general population, the composition of the workforce and the shortage of some skills in the near future. The aim of this study is to explore what the HRM practices are that workers identify in their organizations, as well as the importance they attach to each of these practices, according to their age. A survey was carried out on 528 workers from various companies, to this end. This study showed that the dimensions of “Training; Rewards, Recognition and Participation”; and “Performance Evaluation” are the HRM practices most valued by workers of all ages. The dimension of “Flexible Work Practices” shows the lowest average score for older workers. “Job Security” is the practice that all workers, but particularly the older ones, perceive as being less present in the organization. Workers, in general, value HRM practices more than they perceive them to exist in organizations.